Relationship between crude oil price with foreign exchange rates and interest rates of South East Asian countries - Humaida Banu Samsudin,; Yap, Chiou Shin (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study measures long run relationships and short run relationships between crude oil price, foreign exchange rates and interest rates by using monthly data of Brent crude oil prices with foreign exchange rates and interest rates for seven Southeast Asian countries from January 2010 to October 2017. The long run relationship is tested using the Johansen cointegration test, while the short run relationship is tested using the Granger causality test. The Vector Error Correction Model (VECM) is built for the country with cointegration between variables. The results of the study show that cointegration is only present for Vietnam and not for six other countries. The Granger causality test found that no causal relationship could be detected between crude oil prices and foreign exchange rates for all tested countries. Unidirectional causalities detected in this study are from interest rates to foreign exchange rates for Brunei and Vietnam and from crude oil prices to Singapore's interest rates